Effects of Green Plasticizer Poly (1, 2-Propylene Glycol Adipate) on the Properties of Polyvinyl Chloride - Xia LIU; Huaying HUANG; Qikui XU (Pige Kexue Yu Gongcheng)
The green and environmentally friendly poly(1, 2-propylene glycol adipate) (PPA) was used as plasticizer to plasticize polyvinyl chloride (PVC). Its effects on mechanical properties, hardness, processing fluidity, heat resistance and solvent resistance of PVC were studied and compared with PVC plasticized by dioctyl phthalate (DOP). Results showed that both PPA and DOP had good effects on plasticizing PVC. As the content of plasticizer increased from 40 parts to 50 parts, the tensile strength of the PPA/PVC/CaCO3 and DOP/PVC/CaCO3 composite materials reduced by 3.25% and 10.16%, respectively. The temperatures of 50% mass loss were 392.22 ℃ for PPA/PVC/CaCO3 and 320.16 ℃ for DOP/PVC/CaCO3. The PPA/PVC/CaCO3 composites exhibited higher mechanical properties and heat resistance. In addition, the mass loss rates of the DOP/PVC/CaCO3 in ethanol, engine oil, and n-octane were 4.51%, 0.52%, and 11.81%, respectively, while the PPA/PVC/CaCO3 with excellent resistance to solvent migration showed no significant mass loss in all solvents. Therefore, the green polyester plasticizer PPA not only can plasticize PVC by replacing DOP, but also has a broader application prospect in the environment of high temperature and solvent migration resistance.